Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pmed.1003055
|View full text |Cite
|
Sign up to set email alerts
|

Housing and child health in sub-Saharan Africa: A cross-sectional analysis

Abstract: Background Housing is essential to human well-being but neglected in global health. Today, housing in Africa is rapidly improving alongside economic development, creating an urgent need to understand how these changes can benefit health. We hypothesised that improved housing is associated with better health in children living in sub-Saharan Africa (SSA). We conducted a crosssectional analysis of housing conditions relative to a range of child health outcomes in SSA. Methods and findings Cross-sectional data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 24 publications
10
67
0
Order By: Relevance
“…Rapid economic and population growth in sub-Saharan Africa means that millions of new houses will be built in the coming decade and millions more existing houses will be retrofitted with modern housing features. 13 Clear and easy pathways therefore need to be created for the implementation of SET and other house improvement interventions. Failing to move forward on housing and malaria would be a monumental missed opportunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid economic and population growth in sub-Saharan Africa means that millions of new houses will be built in the coming decade and millions more existing houses will be retrofitted with modern housing features. 13 Clear and easy pathways therefore need to be created for the implementation of SET and other house improvement interventions. Failing to move forward on housing and malaria would be a monumental missed opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that closing the eaves can reduce indoor vector abundance 8 , 9 and that closed eaves, together with modern housing elements, such as metal roofs, window screening, and improved doors, are associated with reduced malaria burdens. 10 , 11 , 12 , 13 There is also a body of work exploring the potential to supplement physical barriers by adding insecticides. 14 , 15 , 16 The In2Care (Wageningen, Netherlands) Eave Tube is one such approach, consisting of ventilation tubes made from pieces of polyvinyl chloride (PVC) pipe embedded in a closed eave.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in developed countries usually adopt more stringent definitions, such as more than one person per bedroom, or more detailed definitions considering the occupants’ age, sex, and relationship. We defined household crowding as more than three people per bedroom, which aligns with the United Nations definition and studies conducted in LMICs [ 20 , 36 , 37 ]; this dichotomous definition is an explicit marker that facilitates screening for at-risk children. However, the prevalence of household crowding and the extent of its impact on violent discipline and neglect of children are not comparable to other studies that have adopted different definitions.…”
Section: Discussionmentioning
confidence: 99%
“…We defined household crowding based on the definition of slums developed by the United Nations as more than three de jure household members (i.e., household members that usually live in the household, excluding visitors) per bedroom [ 18 ]. The definition was aligned with recent studies that explored household crowding and its impact on child health in LMICs [ 20 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Governments and organisations must start to recognise the role of housing in health inequalities and support improved housing for all. Housing has been often missed from the global health agenda, looked through the lens of affordability and access, and considered physically adequate when built from finished materials, with sufficient space and having access to water and sanitation [10]. While the recent WHO Housing and health guidelines [11] are a useful starting place, these must be expanded to include other risks (such as lighting levels, mosquito-borne diseases and pests) and be translated for use in the limiting conditions of informal settlements and be adapted to geographic and social contexts.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%